Pengembangan Media Pembelajaran Matematika Berbasis Canva Interaktif Pada Materi Pengukuran Panjang Benda - Nasya Putry Kusumah; Munifa Sahla Adhitia; Putri Ayu Resfani; Alfiana Nurussama; Hafiziani Eka Putri (STKIP Subang, 2025)
This study aims to develop and determine the feasibility and practicality of interactive Canva-based mathematics learning media on the topic of length measurement for third-grade elementary school students. The research employed a qualitative descriptive method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The learning media was developed based on Bruner’s learning theory, incorporating enactive, iconic, and symbolic stages to support students' understanding from concrete to abstract concepts. Data were collected through expert validation sheets, student response questionnaires, and classroom observations. The results of expert validation showed an average feasibility score of 94% indicating that the media was categorized as very valid. In addition, student responses showed a practicality score of 85,83%, categorized as very practical. These findings indicate that the interactive Canva-based learning media is visually attractive, easy to use, and effective in facilitating students' understanding of length measurement. However, minor technical revisions were required, particularly related to audio clarity and sound variation. Overall, the developed learning media is feasible to be used as an alternative learning resource in elementary mathematics instruction.